2021
DOI: 10.1097/iae.0000000000003167
|View full text |Cite
|
Sign up to set email alerts
|

Natural History and Predictors of Vision Loss in Eyes With Diabetic Macular Edema and Good Initial Visual Acuity

Abstract: Purpose: To identify clinical and anatomic factor-associated vision loss in eyes with treatment-naïve diabetic macular edema and good initial visual acuity.Methods: Retrospective cohort study after long-term history of eyes with untreated center-involving diabetic macular edema and baseline visual acuity $ 20/25 seen at the University of California, Davis Eye Center between March 2007 and March 2018. We collected characteristics including diabetes type, hemoglobin A1c, presence of visual symptoms, visual acuit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 30 publications
0
4
1
Order By: Relevance
“…This current study showed that systemic cardiovascular and cerebrovascular accident rates were slightly higher in the ranibizumab group than in the other two groups, but with an no big difference between the three groups regarding these items 28 .…”
Section: Safety Of Intravitreal Anti-vegf Injections In Diabetic Macularcontrasting
confidence: 42%
“…This current study showed that systemic cardiovascular and cerebrovascular accident rates were slightly higher in the ranibizumab group than in the other two groups, but with an no big difference between the three groups regarding these items 28 .…”
Section: Safety Of Intravitreal Anti-vegf Injections In Diabetic Macularcontrasting
confidence: 42%
“…As methods for vitreous body retinal surgery have improved, the rate of blindness among DR patients has declined; however, DME has become the most important factor associated with vision impairment and blindness in diabetic patients. 14 Scholars have recently suggested that the true correlation between diabetes and vision loss is the degree of macular thickening. 15 , 16 Intervening early in macular edema decreases macular thickness and improves visual acuity varying degrees.…”
Section: Discussionmentioning
confidence: 99%
“…56 Even in eyes with good initial VA, a lack of treatment can lead to severe vision loss. 57 Patients with DR are more likely to experience psychological distress, mental illness, and decreased health-related QOL than those with diabetes without eye involvement. 58 In addition, patients with DR/DME are often younger than those with nAMD.…”
Section: Diabetic Retinopathy/diabetic Macular Edema: Review Of Clini...mentioning
confidence: 99%